Investigating and evaluation of the indicators affecting development of child-friendly cultural complexes with an approach to reconciliation with historical spaces (case study: Shiraz) (Nexo Revista Científica, 2020)
The present study aims to investigate the indicators of a child-friendly city and to introduce strategies for designing child-friendly spaces and centers with an approach to reconciliation with historical spaces, in order to advance the city toward a child-friendly city and promote its goals. The present study is descriptive-analytical in terms of nature, applied in terms of purpose, and combined (quantitative and qualitative) in terms of method. This study was conducted in a historical context in Shiraz for children aged 4 to 12 years. In order for location finding and selecting the desired site, the factors were extracted based on theoretical foundations, and according to SWOT table, the weaknesses, strengths, opportunities, and threats of the three sites were analyzed. Finally, using AHP tool, site number 1 was considered as the most suitable site for designing the complex. Then, using quantitative method, the information and factors were analyzed according to the theoretical framework including spatial, physical, and functional factors affecting improvement of quality of the environment, including 21 indicators in the form of 5-point Likert scale from very high to very low using SPSS software. According to the information obtained about the spatial factor of “shape and size of the space” indicator, the physical factor of “color” index and the physical factor of “fantasy” index had the greatest impact on designing children’s cultural center with an approach to reconciliation with Shiraz’s historical spaces. In the end, according to investigations of the theoretical foundations and theories of theorists and the obtained results, architectural solutions and ideas affecting the designing of complexes were presented in the form of solutions for using light, color, geometry and proportions, nature, and shape and size of the space.